Pengaruh Pendidikan Kesehatan Terhadap Perilaku Pencegahan Demensia Pada Lansia - Alvin Abdillah (NHM PRESS, 2019)
Dementia is a sindrom which is characterization with loss of intelectual capacity, involving is not onlycognitive but also leaguange, visospasial ability,personality memory too. Factors that can affect theonset of dementia such as knowledge, persepsion,motivation, information and environment. From eachfactors can be caused of loss in prevention behavior onelderly. To know the influence of health education inprevention of dementia. The Research design of this study is praexsperiments approach with pre post test. The amountof population in this reaseach is 21 elderly in posyanduelderly. From 21 elderly people was taken 16 sampleand the Technique of collectin data was used simplerandom sampling. The result of this research showed that there isincrease in dementia prevention behavior before andafter health education was given. Results of statisticaltests Pairs t-test with a p-value of 0.05 means 0.000 <H1 accepted means there is influence between beforeand after health education is given to the prevention ofdementia on the elderly behavior. The next researchers expected results of thisresearch can serve as preliminary studies to developother research especially on the influence of healtheducation on behaviors of elderly in the prevention ofdementia, in addition, this is should be supported bypuskesmascuold be joined giving healt education aseffort in prevention on elderly, further research needsto be done by expanding the other variables that canaffect the behavior of the elderly in order to get betteragain.